Coverage and determinants of deworming uptake among under-five children in Somalia: A multilevel analysis of the 2020 SDHS data - Abdirahman Omer Ali; Awo Mohamed Kahie; Muhyadin Yusuf Dahir; Suhaib Mohamed Kahie; Abdisalam Mahdi Hassan; Md. Moyazzem Hossain (PLoS ONE, 2025)
Background Soil-transmitted helminth (STH) infections are a major public health concern in Somalia, particularly affecting the health and development of children under five. Therefore, this study aimed to assess the coverage of deworming uptake and identify associated multilevel factors with deworming uptake among Somali children aged 12–59 months using a Multilevel logistic regression model. Methods This study analyzed data of 15,074 children aged 12–59 months from the 2020 Somalia Demographic and Health Survey (SDHS). Chi-square test and multilevel logistic regression were used to examine individual (maternal/child characteristics, health service use) and community (residence, region) factors associated with non-receipt of deworming medication (poor uptake). Results Only 8.0% of children had received deworming medication, indicating critically low national coverage. The variations of poor deworming uptake among children of different ages in months were 92.91% between 12–15 months, 91.75% between 16–19 months, and 91.26% between 20–59 months. Poor deworming uptake was varied among maternal age groups, with rates of 92.10% (15–24 years), 91.89% (25–34 years), and 91.60% (35–49 years). Findings depict that significant regional variations existed. Better uptake was associated with higher maternal age and education, greater wealth, maternal employment, health facility delivery, and urban/nomadic residence (vs. rural). Residing in urban (AOR: 0.65; 95% CI: 0.51, 0.82, p < 0.05) or nomadic areas (AOR: 0.40; 95% CI: 0.32, 0.49, p < 0.05) was significantly associated with lower odds of poor uptake compared to rural areas. Unexpectedly, children without recent episodes of diarrhea had significantly higher odds of not receiving deworming treatment (AOR = 6.26). Conclusion Low deworming coverage among under-5 children in Somalia is observed. Factors include higher maternal education, greater wealth, health facility delivery, urban or nomadic residence compared to rural, and older child age are significantly associated with deworming coverage. To improve the deworming coverage, organizing school-based campaigns and deploying mobile health teams for door-to-door visits in remote areas may be useful.